The management of early childhood physical development centers at the regional level - Rapoport L.A.; Tomilova S.V.; Prokhorova O.I.; Rapoport A.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the unique features of the management of early childhood development centers in the Sverdlovsk region. Methods and structure of the study. Theoretical and practical approaches are employed. The research is grounded in the analysis of the operations of the pilot project «Centers for Early Physical Development of Children» in the Sverdlovsk region, which was established in accordance with the order of the Ministry of Sports of Russia, dated November 30, 2022, No. 1119. Within the framework of the pilot project, in 2023, efforts were made to identify and select children with exceptional athletic abilities. Results and conclusions. A plan has been created for the operation of early physical development centers for children, which includes: the creation of supplementary general development programs in the area of physical culture and sports; the training (re-training) of personnel to support the operations of early physical development centers; the preparation of legal regulations to determine the locations of study; and the establishment of state and municipal assignments.